(untitled) (Research, Society and Development, 2025)
Aging is an irreversible physiological process that leads to progressive declines in functional capacity, compromising autonomy and quality of life in older adults. In this context, training modalities that emphasize functional and high-intensity movements, such as CrossFit and High-Intensity Functional Training (HIFT), have been studied as effective alternatives for health promotion and maintenance of independence. The present study aimed to analyze, through an integrative literature review, the influence of CrossFit and HIFT on the functional autonomy of older adults. The research was conducted in the SciELO, Google Scholar, and Virtual Health Library (VHL) databases, between 2020 and 2025, using descriptors in Portuguese and English, and eight studies that met the eligibility criteria were included. The results showed that HIFT and related modalities promote significant improvements in strength, mobility, balance, cardiorespiratory capacity, and cognition, in addition to contributing to psychosocial aspects such as self-esteem, motivation, and social engagement, which are crucial for long-term adherence. However, a scarcity of publications specifically addressing CrossFit applied to older adults was observed, as well as a lack of standardization in intervention protocols, which limits comparisons between studies and the generalization of results. It is concluded that CrossFit and HIFT represent promising strategies to foster active and healthy aging, integrating physical, cognitive, and psychosocial benefits that expand functional independence, while highlighting the need for longitudinal and methodologically standardized studies that more specifically investigate the effects of CrossFit in older adults.